Inhaled nitric oxide: are expectations justified? - I. A. Kozlov (Вестник анестезиологии и реаниматологии)
Nitric oxide (NO) is a cellular signaling molecule that causes smooth muscle relaxation in the vascular wall. Inhaled NO (iNO) has been used in intensive care for more than three decades. In Russia, this method was tested in the late 1990s. iNO acts as a selective pulmonary vasodilator, it effectively reduces pulmonary artery pressure and intra-pulmonary blood shunting. In patients with acute respiratory distress syndrome, iNO is used to improve oxygenation, but its role remains controversial. In cardiac surgery, numerous studies have reported the positive effect of iNO on pulmonary hypertension and the elimination of dysfunction and/or insufficiency of the right ventricle. Yet, various studies have failed to demonstrate significant differences in long-term clinical outcomes. Many clinical applications have been proposed at using iNO as a preventive measure for ischemic-reperfusion injury of various organs associated with cardio-pulmonary bypass. iNO has been used with evidence-based efficacy in neonatology in infants with persistent pulmonary hypertension. Yet, various studies have failed to demonstrate significant differences in long-term clinical outcomes for different use cases and applications in critical care medicine. Further studies of iNO are needed, possibly based on the phenotyping of patients’ sensitivity to iNO.